A Case Report of Quinine-Induced Thrombotic Microangiopathy Successfully Treated With Eculizumab - Jun Yen Ng BMedSci (Hons); Douglas Lenton MBBS, FRACP, FRCPA; Ian Kerridge BA, BMed (Hons); Charmaine Wong MBBS, FRACP, FRCPA (SAGE Publishing, 2024)
Drug-induced thrombotic microangiopathy (DITMA) is a life-threatening condition which may be immune or nonimmune mediated. Quinine is the most implicated drug in immune-mediated DITMA. However, the optimal treatment is unclear. Complement inhibition by eculizumab has demonstrated success in many DITMA (e.g., carfilzomib, gemcitabine, and tacrolimus), but there are limited data in DITMA, including quinine-associated cases. A 55-year-old female was diagnosed with quinine-associated thrombotic microangiopathy (TMA), as confirmed by a positive quinine-dependent platelet-associated antibody. This was successfully treated with eculizumab with complete resolution of thrombocytopenia and anemia by 1 and 6 weeks. She required hemodialysis for a month and gained full recovery of renal function. We discuss various challenges with the diagnosis and management of DITMA. We also review published data on the use of eculizumab in various DITMA. Our case demonstrates successful treatment of quinine-induced TMA with eculizumab. We recommend further studies to assess the efficacy of complement inhibition in quinine and other DITMA.